The Characteristics of Premarital Couple Related to Couple’s Knowledge of Healthy Pregnancy Preparation - Juli Oktalia; Herlyssa Herlyssa; Indra Supradewi; Ani Kusumastuti; Ira Budi Pratiwi (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
A well-planned pregnancy procedure will benefit the fetus's health and the mother's physical and psychological adaption to pregnancy. Unwanted pregnancies and on-time pregnancies in a woman might be classified as situations of unmet need. Along with pregnancy, this influence on the mother's unpreparedness to conceive can even lead to the decision to undergo an unsafe abortion. This study aimed to elicit data on the features of premarital couples' preparation for a safe pregnancy and their association with knowledge about pregnancy preparation. The study used a cross-sectional design and purposive sampling to examine 57 premarital couples and then utilizing the chi-square to analyze data. The study's findings indicate that respondents will marry at a high risk of pregnancy. There are still some couples who lack adequate knowledge about pregnancy preparation and have not received adequate counseling. There is a significant relationship between the bride and groom's ages and their level of knowledge about preparing for a healthy pregnancy (p-value 0.000), level of education and level of knowledge (p-value 0.000), perspective and level of knowledge (p-value 0.000), and history of exposure to information and level of knowledge (p-value 0.000). Increased marriage age, greater education level, and provision of relevant information will assist married couples in supporting increased knowledge that is more adequate for pregnancy preparation.